2018
DOI: 10.1186/s12898-018-0207-7
|View full text |Cite
|
Sign up to set email alerts
|

Fox sightings in a city are related to certain land use classes and sociodemographics: results from a citizen science project

Abstract: BackgroundRed foxes (Vulpes vulpes L.) have become successful inhabitants of urban areas in recent years. However, our knowledge about the occurrence, distribution and association with land uses of these urban foxes is poor, partly because many favoured habitats are on private properties and therefore hardly accessible to scientists. We assumed that citizen science, i.e. the involvement of the public, could enable researchers to bridge this information gap. We analysed 1179 fox sightings in the city of Vienna,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…Coyote ranging patterns, which are typically wide and temporally unpredictable, can be difficult to study without the use of costly and intrusive electronic-tracking devices. Fortunately, the gathering of opportunistic public sightings has been proven effective at overcoming these challenges in previous studies of urban carnivores (Lukasik & Alexander, 2011;Poessel et al, 2013;Quinn, 1995;Walter et al, 2018;Weckel et al, 2010;Wine et al, 2015). In addition, by engaging the community in the collection of data, PPSR can also promote broad public education and potentially mitigate human-wildlife conflict (Dickinson et al, 2012;Larson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Coyote ranging patterns, which are typically wide and temporally unpredictable, can be difficult to study without the use of costly and intrusive electronic-tracking devices. Fortunately, the gathering of opportunistic public sightings has been proven effective at overcoming these challenges in previous studies of urban carnivores (Lukasik & Alexander, 2011;Poessel et al, 2013;Quinn, 1995;Walter et al, 2018;Weckel et al, 2010;Wine et al, 2015). In addition, by engaging the community in the collection of data, PPSR can also promote broad public education and potentially mitigate human-wildlife conflict (Dickinson et al, 2012;Larson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This included mostly any incidental observational data by city inhabitants or cases of traffic collisions. Such data was already used by other researchers to study encounters between carnivores and humans or urban population trends 15 , 21 , 28 , 31 , 70 and here we wanted to evaluate its usefulness in future studies. We showed that the probability of reporting on incident involving red foxes was dependent on different temporal variables.…”
Section: Discussionmentioning
confidence: 99%
“…These species are widespread generalists. For example, the red fox has shown to adapt to human facilitated disturbances by changing their home range size to cover more territory (Walter et al 2018;Walton et al, 2017). In Australia, human based disturbances are aiding in the population growth of the invasive red fox (Hradsky et al, 2017).…”
Section: Introductionmentioning
confidence: 99%